The social behavior of older animals - Dagg, Anne Innis (Book collections on Project MUSE., 2009)
At once instructive and compelling, this theme-spanning book reveals the complex nature of maturity in scores of social species and shows that animal behavior often displays the same diversity we find in ourselves.